Experimental study on the impacts of heatwaves with different duration and frequency on the common starfish Asterias rubens - Wolf, Fabian; Seebass, Katja (PANGAEA, 2022)
Experimental study on the performance of the common sea star Asterias rubens subjected to heatwaves of different duration and frequency (No, Interrupted, Present-day, and Extended). Treatments are based on the climatological analysis of 22-year long temperature data. The study was conducted at GEOMAR, Helmholtz-Centre for Ocean Research Kiel (54.329979 N, 10.148013 E) in the Kiel Indoor Benthocosms (Pansch and Hiebenthal 2019) over 68 days from July 5th to September 10th, 2019. The temperature was logged over the entire experimental period (EnvLogger, ElectricBlue, Vairão, Portugal) and measured with a handheld thermometer at least every three days (TTX 110 type T, Ebro, Ingolstadt, Germany). Salinity, pH, and oxygen concentration were also measured over the experimental period (Multi 3630 IDS, WTW, Kaiserslautern, Germany). Sea star feeding rate was quantified by measuring the shell length of consumed blue mussels (Dial Caliper DialMax Metric, Wiha Division KWB Switzerland). Based on a previously described relationship between shell size and tissue dry weight for mussels in the study area (Morón Lugo et al. 2020), the dry weight of consumed mussels was estimated. Sea star individuals were weighed at the start of the experiment, right before the heatwaves started, before the Present day heatwave started to decline, before the Extended heatwave started to decline, and at the end of the experiment. Sea star activity was measured as the time an individual needed to fully turn back to their oral side after being placed on its aboral side (i.e., righting time). These measurements were taken at the start of the experiment, right before the heatwaves started, before the Present day heatwave started to decline, before the Extended heatwave started to decline, and at the end of the experiment.
Keywords: Asterias rubens; environmental variability; Experiment; heatwaves; sea star